2022
DOI: 10.3389/fncel.2022.833186
|View full text |Cite
|
Sign up to set email alerts
|

The Cellular Senescence Factor Extracellular HMGB1 Directly Inhibits Oligodendrocyte Progenitor Cell Differentiation and Impairs CNS Remyelination

Abstract: HMGB1 is a highly conserved, ubiquitous protein in eukaryotic cells. HMGB1 is normally localized to the nucleus, where it acts as a chromatin associated non-histone binding protein. In contrast, extracellular HMGB1 is an alarmin released by stressed cells to act as a danger associated molecular pattern (DAMP). We have recently determined that progenitor cells from multiple sclerosis patients exhibit a cellular senescent phenotype and release extracellular HMGB1 which directly impaired the maturation of oligode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…Furthermore, iNOS-mediated cytokine-induced nitric oxide excess can cause tissue damage in the central nervous system of EAE ( 124 ). Cellular senescence is a cellular feature of MS progenitor cells, and senescent neural progenitor cells can secrete HMGB1 oligodendrocyte progenitors (OPCs) to mature into myelinating oligodendrocytes (OLs), promoting chronic demyelination ( 125 , 126 ).…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…Furthermore, iNOS-mediated cytokine-induced nitric oxide excess can cause tissue damage in the central nervous system of EAE ( 124 ). Cellular senescence is a cellular feature of MS progenitor cells, and senescent neural progenitor cells can secrete HMGB1 oligodendrocyte progenitors (OPCs) to mature into myelinating oligodendrocytes (OLs), promoting chronic demyelination ( 125 , 126 ).…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…Extracellular HMGB1 acts as a damage-associated molecular pattern (DAMP) molecule which induces inflammation to the site of tissue damage (40, 41). However, under normal conditions, HMGB1 is localized in the nucleus as a chromatin associated non-histone binding protein (42). In senescent cells, HMGB1 translocates from the nucleus to the cytoplasm to be secreted (43) and it modulates senescence by binding to the surface of immune cells to initiate the signaling pathway responsible for the expression of pro-inflammatory cytokines (40).…”
Section: Resultsmentioning
confidence: 99%
“…2b ), but secretion of IL-1β and TNFα was not detected in any of the conditions. According to literature, HMC3 cells are unable to secrete TNFα (31) whereas the expression of IL-1β has been verified at both mRNA and protein level by western blot, but its secretion in the media remains elusive, possibly due to high turnover rate of the mature protein (42, 43). Importantly, secretion of both IL-6 and IL-8 was increased at baseline in SLO-treated cells, in line with the senescent-like profile exhibited by these cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study by Rouillard et al 38 showed that extracellular HMGB1 impaired OPC differentiation and remyelination process in the spinal cord of a multiple sclerosis animal model. However, the study had many differences in design compared to our present study, including disease models and HMGB1 concentrations administered in vitro (1 ng/mL versus 500 ng/mL) and in vivo (0.25 μL, 100 ng/mL versus 1 μL, 1 mg/mL).…”
Section: Discussionmentioning
confidence: 99%